2010
DOI: 10.1002/j.2158-1592.2010.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolving a Theory of Performance‐based Logistics Using Insights From Service Dominant Logic

Abstract: Performance‐based logistics (PBL) represents a strategy for sustaining complex systems following production. Despite several implementations, limited understanding exists regarding PBL and its implications. Research using grounded theory emerged a theoretical framework for PBL. Service dominant logic (SDL) is introduced as a theoretical lens for interpreting the results and understanding how trading partners achieve performance‐based outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
182
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(187 citation statements)
references
References 36 publications
(68 reference statements)
3
182
1
Order By: Relevance
“…Both PBL and non-PBL managers focus on gaining efficiency and effectiveness with regard to inventory management, repair, and overhaul. Yet for the PBL manager, the money spent purchasing spares, repairs, and overhaul is continuously calculated against Explaining the effectiveness of PBL an investment in new materials, processes, and technology that will improve reliability and correspondingly drive out demand for that particular spare part (and its warehouse, inventory, and transportation cost), along with repair or overhaul tasks (Kim et al, 2010(Kim et al, , 2007Randall et al, 2010). The PBL contract uses cost avoidance incentives to focus upstream trading partners on the outcome that matters most to the end-user -an operational system at the lowest possible cost.…”
Section: The Economics Of Pbl: Investment Driven By Cost Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…Both PBL and non-PBL managers focus on gaining efficiency and effectiveness with regard to inventory management, repair, and overhaul. Yet for the PBL manager, the money spent purchasing spares, repairs, and overhaul is continuously calculated against Explaining the effectiveness of PBL an investment in new materials, processes, and technology that will improve reliability and correspondingly drive out demand for that particular spare part (and its warehouse, inventory, and transportation cost), along with repair or overhaul tasks (Kim et al, 2010(Kim et al, , 2007Randall et al, 2010). The PBL contract uses cost avoidance incentives to focus upstream trading partners on the outcome that matters most to the end-user -an operational system at the lowest possible cost.…”
Section: The Economics Of Pbl: Investment Driven By Cost Avoidancementioning
confidence: 99%
“…A strength of SDL is that it considers value from both the perspective of the end customer and from the supplier network, thus making SDL a robust supply chain framework (Lambert and García-Dastugue, 2006). Using this framework, Randall et al (2010) found that practitioners essentially operationalized the outcome of SDL by assigning some measure of performance (e.g. system up time) as the desired customer value proposition.…”
Section: The Economics Of Pbl: Investment Driven By Cost Avoidancementioning
confidence: 99%
“…In the PBL, responsibility of the product/service system management is on the supplier of the system, unlike in the traditional end-user -supplier relationship [29]. PBL is in use in military context and it is "a contractual mechanism".…”
Section: Discussionmentioning
confidence: 99%
“…In performance-based logistics (PBL) responsibility of the product/service system management is on a supplier of the system, unlike in the traditional enduser -supplier relationship [19]. In PBL according to Berkowitz et [20].…”
Section: Performance Based Logistics (Pbl) -A Service Management Modementioning
confidence: 99%